2005
DOI: 10.1080/0003684042000290147
|View full text |Cite
|
Sign up to set email alerts
|

Technological change and wage premium in a small open economy: the case of Korea

Abstract: The aim of this study is to analyse the relationship between technological change and the educational wage premium in Korea. The main findings are as follows. First, the changes in educational wage premium were mostly affected by shifts in the supply of college graduates from 1983 to 1993 while the changes were affected more by the shifts in labour demand from 1993 to 2000. Second, the educational wage premium is greater in the industries with rapid technological change than in the industries with slower techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 29 publications
(38 reference statements)
0
12
1
1
Order By: Relevance
“…The educational reform in 1980 restructured the quota system and increased the number of college graduates dramatically. 8 Choi and Jeong (2005) also show that the skill premium associated with technological change is mostly explained by the returns to workers' unobserved heterogeneities. They use the two-stage double fixed effects, developed by Bartel and Sicherman (1999).…”
Section: Datamentioning
confidence: 93%
See 2 more Smart Citations
“…The educational reform in 1980 restructured the quota system and increased the number of college graduates dramatically. 8 Choi and Jeong (2005) also show that the skill premium associated with technological change is mostly explained by the returns to workers' unobserved heterogeneities. They use the two-stage double fixed effects, developed by Bartel and Sicherman (1999).…”
Section: Datamentioning
confidence: 93%
“…However, despite a continuing influx of college graduates into the labour market, it increased again since the mid-1990s. The recent increase in college wage premium is found to be closely related with the technological change in Korea (Hur et al, 2002;Kang and Hong, 2002;Choi and Jeong, 2005). 8 Considering these dynamics in the labour market, the Korean case would be an ideal setting for testing the hypothesis.…”
Section: Datamentioning
confidence: 98%
See 1 more Smart Citation
“…The rate of technological change across industries is emphasized by referring to cross-sectional approach. Choi and Jeong (2005) add on Bartel and Sicherman (1999) that only workers with higher education get higher wages in those industries. Another study dealing with the question of how technological change is related to changes in wage gaps by schooling, experience and gender puts forward that wage gaps by schooling increases in the most industries with rising R&D intensity and accelerating growth in capital-labour ratio (Allen, 2001).…”
Section: Introductionmentioning
confidence: 98%
“…Studies using industry‐level data (e.g., Hodson and England ; Loh ) or plant‐level data (e.g., Krueger ; Doms, Dunne, and Troske ) have mostly supported a positive influence of technological change regarding wages. However, Bartel and Sicherman () and Choi and Jeong () argued that the positive relationship between technological change and educational wage premium is rather weak after controlling for individual unobserved heterogeneity in the United Kingdom and South Korea, respectively. However, by including occupational or industry fatality rates as explanatory variables in the wage equation, previous studies have generally shown that job risk has a significantly positive impact on wages (e.g., Leeth and Ruser ; Hartog et al .…”
Section: Introductionmentioning
confidence: 99%